Early Perspectives on the Planned Brazilian Program to Address Ship-Sourced Pollution - Zacharias, Daniel Constantino; Lemos, Angelo Teixeira (Journal of marine science and engineering, 2025)
A new integrated multi-user monitoring system for Brazilian Jurisdictional Waters (BJW), developed by Instituto Nacional de Pesquisas Espaciais (INPE) with participation from leading universities and research centers in Brazil, proposes a national approach to address oil spills in the South Atlantic. The system incorporates a range of technologies, such as satellite data, AI algorithms, autonomous sensors, and high-resolution modeling, to detect and respond to oil spills and maritime threats. This initiative not only aims to strengthen Brazil’s readiness to address the oil spills but also contribute to the protection of BJW resources and ecosystems. This opinion paper presents third-party viewpoints on SisMOM, analyzing both the positive and negative aspects of the project. It also explores some expectations for SisMOM, including some main and alternative methodologies. This article only reflects the authors’ perspectives, interpretations, points of view, opinions, and discussions about SisMOM’s propositions. This paper does NOT represent an official communication of the program, nor its methodologies and developments.